Comparison of The Effectiveness of Decil of Bangun-Bangun Leaf with Cassava Leaves in The Production of Breast Milk - Shennitha Yusibbrahka; Bunga Tiara Carolin; Vivi Silawati (Health and Technology Journal (HTechJ), 2023)
Based on a report by the Central Statistics Agency, the percentage of exclusive breastfeeding in the capital city decreased by 5,23% compared to the previous year. The low level of exclusive breastfeeding will impact the quality and viability of the next generation. Efforts to increase the coverage of breast milk can be made by non-pharmacological methods, one of which is by consuming wake-up leaves and cassava leaves containing galactagogue and vitamin A for breast milk. The aim of this study is knowing the comparison the effectiveness of giving a decoction of wake-up leaves with cassava leaves in breast milk production at PT. Jakarta Medica Administration in 2023. This study used a two-group pretest and posttest design. A sample of 32 respondents after giving birth 40 days to 50 days was taken using a non-probability sampling technique. The instruments used were Breast Milk Production Observation Sheets and SOPs for interventions. The data normality test used Shapiro Wilk and data analysis using the Paired T-Test and Independent T-Test. The average volume of breast milk increased after being given the intervention of 361,25 ml of guava leaves and 256,25 ml of cassava leaves. The results of the Paired T-Test showed a p-value of 0,71 which means that both interventions were effective in increasing breast milk volume. Based on the average value of the two interventions that experienced an increase in breast milk production, the results of the Paired T-Test showed a p-value of 0.71, which means that both interventions were effective in increasing breast milk volume. and There is no difference in the effectiveness of Bangun-Bangun leaves and cassava leaves for breast milk production, but Bangun-Bangun leaves are more effective for increasing milk production.